PERJANJIAN KREDIT KEPEMILIKAN RUMAH (KPR) BERDASARKAN HUKUM CESSIE - Dendy Pratama Achmady; Jarot Widya Muliawan (Gapenas Publisher, 2023)
Home Ownership Loans (HOL) are usually held by banks. However, in practice mortgage problems often occur, one of which is bad credit. The solution that is often carried out by banks as creditors is to transfer the receivables (cessie) to the object of mortgage rights. This study uses normative research methods. This study discusses the home ownership credit agreement in transferring cessie receivables and the legal consequences of not granting a cessie to the debtor. The results of the analysis show that the process of transferring receivables by the first party to a third party in making a cessie deed, whether authentic or private, requires notification to the debtor or in writing to be approved and known by the debtor as described in Article 613 of the Civil Code and the legal consequences of the transfer receivables from old creditors to new creditors